Capital Flows and Economic Fluctuations : The Role of Commercial Banks in Transmitting Shocks - Zhou, Yong Sarah (IMF Working Papers; Working Paper ;, 2008)
This paper uses a general equilibrium model to examine the central role played by commercial banks in intermediating and amplifying the capital flow shocks to the local economy in the 1997 Asia financial crisis. It finds that a sudden stop of capital inflows affects the equilibrium credit supply through two channels: first, the plunge of foreign financing decreases the loanable funds directly; and second the sudden stop drives up the cost of providing banking services, thereby additionally reducing the available bank credit to firms through a "deposit run". Empirical results from a VAR model broadly support the theoretical implications.